2021
DOI: 10.1039/d1nj01696b
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal-catalyzed C–H functionalizations of indoles

Abstract: Over the last two decades, transition-metal catalyzed C-H functionalization of indoles has emerged as an area of extensive research and tremendous progress has been made in this regard. Early developments...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 308 publications
0
21
0
Order By: Relevance
“…Indole is a kind of important biologically active naturally occurring alkaloid, and it also constitutes representative core architecture for extensive pharmaceutical molecules . Consequently, direct functionalization on the indole ring became one of the most straightforward protocol for rapid access to structure and property diversified indole derivatives . It is well-known that both C2- and C3-positions of indole exert much higher reactivity than the other positions; thus, it remains a long-standing challenging topic to install functional groups on the benzenoid moiety of the indole skeleton .…”
mentioning
confidence: 99%
“…Indole is a kind of important biologically active naturally occurring alkaloid, and it also constitutes representative core architecture for extensive pharmaceutical molecules . Consequently, direct functionalization on the indole ring became one of the most straightforward protocol for rapid access to structure and property diversified indole derivatives . It is well-known that both C2- and C3-positions of indole exert much higher reactivity than the other positions; thus, it remains a long-standing challenging topic to install functional groups on the benzenoid moiety of the indole skeleton .…”
mentioning
confidence: 99%
“…6 Transition-metal-catalyzed C−H activation is a fascinating and complementary strategy for the direct functionalization of indoles. 7 We achieved branch selectivity in the Ir-catalyzed C− H alkylation of indole with styrene by the combination of a directing group (DG) on the nitrogen atom and diphosphine ligand. 8 While we further examined an enantioselective reaction, the ee was moderate (43% ee).…”
mentioning
confidence: 99%
“…Whereas, a mixture of both these fluorinated solvents resulted in only a slight improvement in the yield (Table S1, entry 4). Next, we varied the silver-based additives such as AgSbF6 and AgNTf2 instead of AgBF4, but no improvement in yield was observed (Table S1, entry [5][6]. The amount of copper acetate and its variation from Cu(OAc)2 to AgOAc was also not helpful for obtaining a better result (Table S1, entry 7-8).…”
Section: Resultsmentioning
confidence: 98%
“…4 In this context, the sp 2 C-H bond functionalisation of indole at the C3 position has been accomplished through directed (Figure 1a), as well as non-directed pathways. 5 Among these two types of metalation, the directed sp 2 C-H functionalisation has been explored by installing a directing group at the C2 position. Benjamin Pelcman et al have previously reported the palladium and platinum-catalysed acetoxylation of indole at C3 position using C2 ester as coordinating group.…”
Section: Introductionmentioning
confidence: 99%